Extraction Center Pixel Coordinates from Human Body Laser Stripe Image with Bezier Curve Fitting Method (Journal of Fiber Bioengineering and Informatics, 2015)
The main goal of this study is to improve the performance of laser rotating of non-contact human bodyscanning system, and to get the true and accurate 3D information of measured human body. In theaspect of obtaining the human body pixel coordinates, the extraction accuracy of laser stripe center is oneof the important factors to affect the measurement accuracy. Therefore, this paper mainly discussed thealgorithm of obtaining and the curve fitting human body scanning laser stripe center pixel coordinates.In the analysis of the characteristics of the human body laser stripe images, put the improved columnprocessing algorithm to compute stripe center position. Using the Bezier curve fitting of the humanbody scanning light trap center line, effectively improved the smoothness of the human body scanninglight trap center line.